1994
DOI: 10.1007/bf01839261
|View full text |Cite
|
Sign up to set email alerts
|

The use of discriminant analysis in predicting the distribution of bluetongue virus in Queensland, Australia

Abstract: The climatic variables that were most useful in classifying the infection status of Queensland cattle herds with bluetongue virus were assessed using stepwise linear discriminant analysis. A discriminant function that included average annual rainfall and average daily maximum temperature was found to correctly classify 82.6% of uninfected herds and 72.4% of infected herds. Overall, the infection status of 74.1% of herds was correctly classified. The spatial distribution of infected herds was found to parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similar stress effects could suppress populations of C. bolitinos in hotter environments. Modelling done on an allopatric, identical sister species C. brevitarsis in Australia found that mean maximum temperatures could predict BTV infection (and thus C. brevitarsis distribution) with an accuracy of ~75% [ 50 ]. Considering the notable similarity of C. bolitinos and C. brevitarsis in morphology, habitat and habit, it is possible that it could be similarly employed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar stress effects could suppress populations of C. bolitinos in hotter environments. Modelling done on an allopatric, identical sister species C. brevitarsis in Australia found that mean maximum temperatures could predict BTV infection (and thus C. brevitarsis distribution) with an accuracy of ~75% [ 50 ]. Considering the notable similarity of C. bolitinos and C. brevitarsis in morphology, habitat and habit, it is possible that it could be similarly employed.…”
Section: Discussionmentioning
confidence: 99%
“…The negative and positive results of iELISA test were classified as 0 and 1 respectively. Mean value of each climate parameter corresponding to the location of sample collection was analyzed using linear discriminant analysis (Ward 1994) to determine the parameter discriminating the negative and positive sample…”
Section: Linear Discriminant Analysismentioning
confidence: 99%